Residual heparin concentrations in salvaged blood from the Sorin Xtra® autotransfusion system during cardiac surgery - Buys, Mathilde (Stellenbosch : Stellenbosch University, 2016)
Thesis (MMed)--Stellenbosch University, 2016.